Strategic psychological warfare of the Truman Administration : - Wood, Nelson Ovia (My University, 1982)
This study is concerned with the origins, objectives, and operations of the Truman Administration's strategic psychological warfare effort.

Between 1946 and 1952, the Truman Administration originated and used an unprecedented organization to project the American image worldwide, during a period of peace. Though enduring many name changes, the organization was most often known as the United States Information and Educational Exchange Agency (U.S.I.E.).

U.S.I.E. was given the task of supporting and assisting United States foreign policy and countering Soviet propaganda throughout the world. Three major periods of operations are discerned, dealing with a particular employment philosophy as approved at the National Security Council. During the period studied, U.S.I.E. propaganda changed from the philosophy of a "full and fair" picture of the United States to one of countering Soviet propaganda and attacking Soviet principles and leadership.
Keywords: History, United States.